Administrative Management in the Implementation of School Administrative Services at SMKN 1 Gowa - Arni Nasira; Sirajuddin Saleh; Sitti Hardiyanti Arhas (ASHA Publishing, 2025)
Learning facilities have a major role in improving the quality of learning. Adequate facilities can create This study aims to determine the description of administrative management in carrying out school administration services at SMKN 1 Gowa. This study focuses on planning, organizing, implementing, and supervising school administration services. The research instruments used are observation and interview guidelines. The data collection technique employed in this study involves testing for data validity through credibility assessment. The data obtained were analyzed using the Miles, Huberman, and Saldana analysis model. Based on the results of the study, it shows that administrative management in carrying out administrative services at SMKN 1 Gowa is in a